Культуротворческая миссия современного социально-гуманитарного образования - Вишневский, Михаил Иванович (НТУ "ХПИ", 2012)
The author reveals the features of the social and humanities education in which general cultural content is closely linked with the personal aspects of life culture. In particular, notes that it is the social and humanities education is a form of self-development of modern culture.
Keywords: социально-гуманитарное образование; мировоззрение личности; эпоха модерна; религиозный ренессанс